A Conceptual Design of Teacher-Learner Framework for Educational Serious Games - Yusof, Amri; Crowder, Richard M.; Gilbert, Lester; Wills, Gary (Journal of ICT in Education, 2014)
This paper introduces a conceptual Teacher-Learner framework for collaborative learning with serious games. An initial study identified 12 attributes of educational serious games that can be used to support effective learning. These attributes can be applied to the development of a conceptual framework for games to support learning. A considerable number of serious games have been developed over the 10 years, with varying degrees of success. Due to a lack of clear standards and guidelines for game developers, it is difficult to justify claims that a specific game meets the learners’ requirements and/ or expectations. This paper provides an account of a conceptual framework for serious games that will guide their designs and the measurement of achievements in meeting the learners’ requirements.